Awards of Best Poster Presentation entitled Lack of association of single nucleotie polymorphisms IL-6-174G> and PPARyPro12Ala with sporadic colorectal cancer predisposition risk in Malaysian population , June 2011 - Mohd Aminudin, Mustapha; Siti Nurfatimah, Mohd Shahpudin; Ahmad Aizat, Abdul Aziz; Zaidi, Zakaria; Shanwani, A.M.S.; Mohammad Radzi, A.H.; Ankathil, Ravindran (Organised by School of Medical Sciences, USM, 2011)
16th National Conference on Medical and Health Sciences. 22-23rd June 2011.